HUBUNGAN POLA MAKAN DENGAN KEJADIAN ASAM URAT PADA LANSIA DI DUSUN ANGSANA DESA SANGANOM KECAMATAN NGULING KABUPATEN PASURUAN : The Relationship of Eating Pattern with Uric Acid for The Elderly in Angsana hamlet, Sanganom Village Nguling District, Pasuruan Regency - Rina Widiyawati; Siti Muthoharoh (Forind Press, 2023)
There are still many elderly people who do not know about healthy eating patterns, whether it is the type of food, and the amount of food so that many people get sick because of wrong eating patterns. One of them is gout. Correlation research design with cross sectional approach and sampling method with probability sample technique. The population is 60 elderly. With a sample of some of the elderly as many as 52 elderly. The instrument in this study used a questionnaire. Analysis using Spearman test. The results of this study were obtained who have eating patterns in the category of sometimes as many as 29 respondents (55.8%). And those who have an eating pattern in the rare category are 23 respondents (44.2%). Meanwhile, in the incidence of gout, almost all respondents had high uric acid incidence as many as 40 respondents (76.9%). And normal as many as 11 (21.2%). And low as much as 1 (1.9%). The results of the statistical test of the spearman rho test with a correlation coefficient of p = 0.004 (p = 0.004 < = 0.005). It can be concluded that the variable diet has a significant relationship with the incidence of gout and there is a relationship between diet and the incidence of gout in the elderly. Elderly with an unhealthy diet have high uric acid levels (Lk: > 7.0 Pr : > 6.0), while the elderly with a healthy diet have normal uric acid levels (Lk: 3.5-7.0 Pr: 2.6-6.0). Most elderly have unhealthy eating patterns, and it is found that most elderly have high uric acid levels.